Risk Factors and Neonatal Outcome in Patients with Placental Abruption (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To determine the risk factors and perinatal outcome in patients with placental abruption.Design: Case control study.Setting: Department of Obstetrics and Gynaecology, Sir Ganga Ram Hospital, Lahore.Methods: All patients presenting with antepartum haemorrhage due to placental abruption at gestation 28 weeks or above were included in study. Other cases of antepartum haemorrhage like placenta previa, vasa previa, cervical or vaginal local pathology were ruled out. Detailed information was collected from the patient regarding her demographic profile, age, parity, previous history of placental abruption. History of pregnancy induced hypertension, any history of smoking or substance abuse or history of fall were recorded on predesigned proforma for the purpose of study.Neonatal outcome was also recorded including gestational age at delivery, birth weight, APGAR score at 1min and 5 min interval